Managing disaster risk in emerging economics - Kreimer, Alcira (Ed.); World Bank; Arnold, Margaret (Ed.) (Washington World Bank, 2000)
This volume presents papers connected to several events organised by the World Bank Disaster Management Facility(DMFfocused on creating strategic partnerships to reduce the impacts of disasters on developing countries.The first eventJune 1999 on how to co
Keywords: Emergency management-Economic aspects-Developing countries; Emergency management-Developing countries-Planning; Disaster relief-Economic aspects-Developing countries; Disaster relief-Developing countries-Planning